Palaces for the People: Scrutinizing Social Infrastructure in Sulaimani. (1st January 2018) - Levkowitz, Joshua
Abstract : This essay considers the public spaces of the Chaikhana, or teahouse, as a traditional place for public assembly and the newly renovated "Old" Tobacco Factory, as a new art space. Utilizing Eric Klinenberg's concept of social infrastructure, Levkowitz critically examines these public spaces in Kurdish society wherein members of a community may go to participate in the social life of their community, come together to develop and maintain social relationships and to produce knowledge. The challenge for social infrastructure in Kurdistan today is that most existing public spaces are owned or controlled by individuals and groups who are part of or aligned with either one of the two of Kurdistan's major political parties, the KDP (Kurdistan Democratic Party) or the PUK (Patriotic Union of Kurdistan) who have done little to foster true social infrastructure which has left a vacuum into which the private sector has filled.